Grafting on resistant rootstocks alleviates salt stress on tomato by enhancing morpho-physiological and biochemical traits - Md Sarowar Alam; Mark Tester; Gabriele Fiene; Gordon Wellman; Magdi Ali Ahmed Mousa (Protoplasma, 2026)
Salinity is a global threat to crop production, reducing yields and jeopardizing food and nutrition security. This study was performed to evaluate the salinity tolerance of high-yielding commercial tomato ‘Super Sweet F 1 ’(SS), which was self-grafted, or cross-grafted with salt-tolerant rootstocks ‘Maxifort F 1 ’ (MF), ‘Pimp-M021’(PM), and ‘Ramsi’ (RM). The plants were evaluated at low (18.2 mM NaCl) and high-water salinity (150 mM NaCl). The cross-grafted plants SS/MF and SS/PM showed similar responses under high salinity with increased leaf chlorophyll concentration, relative water content (RWC), membrane stability index (MSI), Na + and K + concentration, electrolyte leakage (EL), stomatal conductance, fruit number, and weight, when compared to non-grafted and self-grafted plants. Due to the salt stress, elevated activities of proline, total phenols (TPC), total flavonoids (TFC), polyphenol oxidase (PPO; EC 1.14.18.1), peroxidase (POD; EC 1.11.1.7), catalase (CAT; EC 1.11.1.6), and superoxide dismutase (SOD; EC 1.15.1.1) were also measured in the leaves of SS/MF, SS/PM, and SS/RM in comparison with SS and SS/SS. The principal component biplot analysis confirmed that the grafted tomatoes, SS/MF and SS/PM, showed improved performance under salt stress compared with non-grafted, self-grafted, and cross-grafted SS/RM plants. This study revealed that Pimp-M021’(PM) could be a promising candidate beside the commercial Maxifort F 1 (MF) rootstock for tomato under salt stress conditions. Our findings demonstrated the positive effects of salt-tolerant rootstocks on tomato growth, yield, and fruit characteristics, and this could herald a sustainable tomato production practice in salinity-prone areas worldwide.

Developing and ranking a national red list of Saudi Arabian plants through meta-analysis - Christopher Clarke; Zahra Alhawsa; Simon John Attwood; Sarah Alsaidalani; Mark Tester (Biological Conservation, 2026)

How greenhouse horticulture in arid regions can contribute to climate-resilient and sustainable food security - Simon Goddek; Oliver Körner; Karel J. Keesman; Mark A. Tester; Ryan Lefers; Luuk Fleskens; Alyssa Joyce; Erik van Os; Amit Gross; Rik Leemans (Global Food Security, 2023)

PlantACT! – how to tackle the climate crisis - Heribert Hirt; Salim Al-Babili; Marilia Almeida-Trapp; Antoine Martin; Manuel Aranda; Dorothea Bartels; Malcolm Bennett; Ikram Blilou; Damian Boer; Alix Boulouis; Chris Bowler; Sophie Brunel-Muguet; et al. (Trends in Plant Science, 2023)

Genetic networks underlying salinity tolerance in wheat uncovered with genome-wide analyses and selective sweeps - Danting Shan; Mohsin Ali; Mohammed Shahid; Anjuman Arif; Muhammad Qandeel Waheed; Xianchun Xia; Richard Trethowan; Mark Tester; Jesse Poland; Francis C. Ogbonnaya; Awais Rasheed; Zhonghu He; et al. (Theoretical and Applied Genetics, 2022)

Phenotyping a diversity panel of quinoa using UAV-retrieved leaf area index, SPAD-based chlorophyll and a random forest approach - Jiale Jiang; Kasper Johansen; Clara S. Stanschewski; Gordon Wellman; Magdi A. A. Mousa; Gabriele M. Fiene; Khalid A. Asiry; Mark Tester; Matthew F. McCabe (Precision Agriculture, 2022)
Given its high nutritional value and capacity to grow in harsh environments, quinoa has significant potential to address a range of food security concerns. Monitoring the development of phenotypic traits during field trials can provide insights into the varieties best suited to specific environmental conditions and management strategies. Unmanned aerial vehicles (UAVs) provide a promising means for phenotyping and offer the potential for new insights into relative plant performance. During a field trial exploring 141 quinoa accessions, a UAV-based multispectral camera was deployed to retrieve leaf area index (LAI) and SPAD-based chlorophyll across 378 control and 378 saline-irrigated plots using a random forest regression approach based on both individual spectral bands and 25 different vegetation indices (VIs) derived from the multispectral imagery. Results show that most VIs had stronger correlation with the LAI and SPAD-based chlorophyll measurements than individual bands. VIs including the red-edge band had high importance in SPAD-based chlorophyll predictions, while VIs including the near infrared band (but not the red-edge band) improved LAI prediction models. When applied to individual treatments (i.e. control or saline), the models trained using all data (i.e. both control and saline data) achieved high mapping accuracies for LAI (R 2 = 0.977–0.980, RMSE = 0.119–0.167) and SPAD-based chlorophyll (R 2 = 0.983–0.986, RMSE = 2.535–2.861). Overall, the study demonstrated that UAV-based remote sensing is not only useful for retrieving important phenotypic traits of quinoa, but that machine learning models trained on all available measurements can provide robust predictions for abiotic stress experiments.

Mapping of novel salt tolerance QTL in an Excalibur × Kukri doubled haploid wheat population - Muhammad A. Asif; Rhiannon K. Schilling; Joanne Tilbrook; Chris Brien; Kate Dowling; Huwaida Rabie; Laura Short; Christine Trittermann; Alexandre Garcia; Edward G. Barrett-Lennard; Bettina Berger; Diane E. Mather; et al. (Theoretical and Applied Genetics, 2018)
Key message Novel QTL for salinity tolerance traits have been detected using non-destructive and destructive phenotyping in bread wheat and were shown to be linked to improvements in yield in saline fields. Abstract Soil salinity is a major limitation to cereal production. Breeding new salt-tolerant cultivars has the potential to improve cereal crop yields. In this study, a doubled haploid bread wheat mapping population, derived from the bi-parental cross of Excalibur × Kukri, was grown in a glasshouse under control and salinity treatments and evaluated using high-throughput non-destructive imaging technology. Quantitative trait locus (QTL) analysis of this population detected multiple QTL under salt and control treatments. Of these, six QTL were detected in the salt treatment including one for maintenance of shoot growth under salinity ( QG (1 – 5) .asl - 7A ), one for leaf Na + exclusion ( QNa.asl - 7A ) and four for leaf K + accumulation ( QK.asl - 2B.1 , QK.asl - 2B.2 , QK.asl - 5A and QK:Na.asl - 6A ). The beneficial allele for QG (1 – 5) .asl - 7A (the maintenance of shoot growth under salinity) was present in six out of 44 mainly Australian bread and durum wheat cultivars. The effect of each QTL allele on grain yield was tested in a range of salinity concentrations at three field sites across 2 years. In six out of nine field trials with different levels of salinity stress, lines with alleles for Na + exclusion and/or K + maintenance at three QTL ( QNa.asl - 7A , QK.asl - 2B.2 and QK:Na.asl - 6A ) excluded more Na + or accumulated more K + compared to lines without these alleles. Importantly, the QK.asl - 2B.2 allele for higher K + accumulation was found to be associated with higher grain yield at all field sites. Several alleles at other QTL were associated with higher grain yields at selected field sites.

Marine Microalgae: Climate, Energy, and Food Security from the Sea - Charles Greene; Mark Huntley; Ian Archibald; Léda Gerber; Deborah Sills; Joe Granados; Jefferson Tester; Colin Beal; Michael Walsh; Robert Bidigare; Susan Brown; William Cochlan; et al. (Oceanography, 2016)

Nitrogen assimilation system in maize is regulated by developmental and tissue-specific mechanisms - Darren Plett; Luke Holtham; Ute Baumann; Elena Kalashyan; Karen Francis; Akiko Enju; John Toubia; Ute Roessner; Antony Bacic; Antoni Rafalski; Kanwarpal S. Dhugga; Mark Tester; et al. (Plant Molecular Biology, 2016)

HVP10 encoding V-PPase is a prime candidate for the barley HvNax3 sodium exclusion gene: evidence from fine mapping and expression analysis - Yuri Shavrukov; Jessica Bovill; Irfan Afzal; Julie E. Hayes; Stuart J. Roy; Mark Tester; Nicholas C. Collins (Planta, 2013)

Quantifying the effect of soil compaction on three varieties of wheat (Triticum aestivum L.) using X-ray Micro Computed Tomography (CT) - Saoirse R. Tracy; Colin R. Black; Jeremy A. Roberts; Ann McNeill; Rob Davidson; Mark Tester; Marko Samec; Dean Korošak; Craig Sturrock; Sacha J. Mooney (Plant and Soil, 2012)

Identification of novel quantitative trait loci for days to ear emergence and flag leaf glaucousness in a bread wheat (Triticum aestivum L.) population adapted to southern Australian conditions - Dion Bennett; Ali Izanloo; James Edwards; Haydn Kuchel; Ken Chalmers; Mark Tester; Matthew Reynolds; Thorsten Schnurbusch; Peter Langridge (Theoretical and Applied Genetics, 2012)

Calcium Inhibits Dihydropyridine-Stimulated Increases in Opening and Unitary Conductance of a Plant Ca2+ Channel - Miguel A. Piñeros; Mark Tester (The Journal of Membrane Biology, 2011)

A water-centred framework to assess the effects of salinity on the growth and yield of wheat and barley - Brett N. Harris; Victor O. Sadras; Mark Tester (Plant and Soil, 2010)

HvNax3—a locus controlling shoot sodium exclusion derived from wild barley (Hordeum vulgare ssp. spontaneum) - Yuri Shavrukov; Narendra K. Gupta; Junji Miyazaki; Manahil N. Baho; Kenneth J. Chalmers; Mark Tester; Peter Langridge; Nicholas C. Collins (Functional & Integrative Genomics, 2010)

Glutamate activates cation currents in the plasma membrane of Arabidopsis root cells - Vadim Demidchik; Pauline Adobea Essah; Mark Tester (Planta, 2004)

Correlation between extent of osteolytic damage and metastatic burden of human breast cancer metastasis in nude mice: Real-time PCR quantitation - Angus M. Tester; Julie A. Sharp; Nirada Dhanesuan; Mark Waltham; Erik W. Thompson (Clinical & Experimental Metastasis, 2002)